Georges Gros et le protestantisme - Patrick Cabanel (Revue des Langues Romanes)
Two novels by Georges Gros, Lo Batèu de pèira and Ieu, Bancel, allow us to identify the links of their author with the Protestantism which marked his childhood in Nîmes, and to reflect on the delicate question of the links that can exist between this Protestantism, both religion and memory, and literary creation.